Irsā al-Usus al-‘Ilmīyah li al-Dirāsat al-Islāmīyah: al-Taṭawwur al-Akādīmī li al-Jāmi’at al-Islāmīyah al-Ḥukūmīyah wa al-Ma’āhid al-Islāmīyah al-Ḥukūmīyah al-‘Ulyā bi Indūnīsīyā - Jabali, Fuad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2002)
in the past, the main purpose of IAIN was